2002
DOI: 10.1124/dmd.30.9.1013
|View full text |Cite
|
Sign up to set email alerts
|

Disposition of a Specific Cyclooxygenase-2 Inhibitor, Valdecoxib, in Human

Abstract: ABSTRACT:Valdecoxib is a potent and specific inhibitor of cyclooxygenase-2, which is used for the treatment of rheumatoid arthritis, osteoarthritis, and the dysmenorrhea pain. Eight male human subjects each received a single 50-mg oral dose of [

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 12 publications
(7 reference statements)
0
35
0
Order By: Relevance
“…These metabolites were also detected in human metabolism studies and were confirmed by the comparison with the synthetic standards (Yuan et al, 2002).…”
Section: M4 M6 and M8 The Mass Spectra Of M4 M6 And M8 Showed [Mmentioning
confidence: 63%
See 3 more Smart Citations
“…These metabolites were also detected in human metabolism studies and were confirmed by the comparison with the synthetic standards (Yuan et al, 2002).…”
Section: M4 M6 and M8 The Mass Spectra Of M4 M6 And M8 Showed [Mmentioning
confidence: 63%
“…However, the oxidative breakdown of the N-hydroxy sulfonamide group in M2 led to the formation of a sulfonic acid metabolite M8, which was detected in mouse urine. Both M2 and M8 were found in human urine (Yuan et al, 2002). Reduction of valdecoxib on the isoxazole ring resulted in the formation of an isoxazole ring-opened metabolite M11.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…VALD chemically is 4-(5-methyl-3-phenyl-4-oxazolyl)benzenesulfonamide, and its chemical structures is shown in (Figure 1). VALD is metabolized primarily by cytochrome P450 2C9 and 3A4 to the pharmacological active hydroxylated metabolite and the carboxylic acid metabolite in humans [7][8][9].…”
Section: Introductionmentioning
confidence: 99%